2-3h=10-5h

Simple and best practice solution for 2-3h=10-5h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-3h=10-5h equation:


Simplifying
2 + -3h = 10 + -5h

Solving
2 + -3h = 10 + -5h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '5h' to each side of the equation.
2 + -3h + 5h = 10 + -5h + 5h

Combine like terms: -3h + 5h = 2h
2 + 2h = 10 + -5h + 5h

Combine like terms: -5h + 5h = 0
2 + 2h = 10 + 0
2 + 2h = 10

Add '-2' to each side of the equation.
2 + -2 + 2h = 10 + -2

Combine like terms: 2 + -2 = 0
0 + 2h = 10 + -2
2h = 10 + -2

Combine like terms: 10 + -2 = 8
2h = 8

Divide each side by '2'.
h = 4

Simplifying
h = 4

See similar equations:

| 10-6t=-8-9t | | 8-8x=1-3x | | 4=-v+v/-8 | | -7-5u=-7u+9 | | 4a^2-9a+2=0 | | 9+3g=4g | | 6y+5=4y-9 | | -4-9=-2 | | 5(6x-5)=1-1x | | -5n=5-10n | | 4b+10=-10+2b | | -5w-10=3w+6 | | 8x=100+3x | | 5x+35=2(x+8) | | 2r-6=3r | | S=187+0.225S | | 10-2z=-7z | | -f+3=-4f | | 7*3x=6x+9 | | x+1/3+x-2/6=x+6/12 | | -6j-8=-8j | | 1/4d+3/4=6 | | x+6/3+x-2/6=2x-3/12 | | 27=2-5(9-x) | | 3(t+1)=9 | | 1/2h-16=5/8h | | 8h+(-15h)+(-5)=(-19) | | 9+2x=15-3x | | 7(9+2x)=15-3x | | 4(c+2)=16 | | 4x/(x+2)=2 | | -(x)-6/2=15 |

Equations solver categories